Gender-justice and the development of intersectional thinking: evidence from an intermediate French course. (1st September 2022) - Knisely, Kris Aric
Abstract : Language educators are increasingly recognizing the importance of pedagogies that engage with students as whole persons, particularly from a gender-just and intersectional paradigm. However, action on this ethical impetus is often limited by a nexus of inadequate training, materials, and research. Using data from 112 US undergraduate students of intermediate-level French, this study investigates the possible relationships among gender-just practices and the development of students' intersectional thinking. Results suggest that gender-just pedagogies are a viable tool for increasing students' exposure to, awareness of, and ability to engage in thinking about intersections and intersectionality.